Pengaruh Character Strengths terhadap Teacher Efficacy pada Guru Sekolah Menengah Atas - Kharisma D.W.; Gagan Hartana T.B. (Jurnal Ilmiah Psikologi MIND SET, 2010)
The study aims to examine the effect of character strengths toward teacher efficacy on senior high school teacher. The participants are 79 state run vocational school teachers and senior high school teachers who work in DKI province. Character strengths are measured with a tool modified from VIA-IS (Value in Action Inventory Scale) instrument which was developed by Manuel D. Rhoda Mayerson Foundation. Teacher efficacy is measured with a tool modified from OSTES (Ohio State Teacher Efficacy Sense) instrument which was developed by Tschannen-Moran & Woolfolk Hoy (2001). The result shows a significant effect of character strengths toward teacher efficacy. There are five distinguished strengths borne by age has influence on teacher efficacy.